Social Accountability and Corporate Greenwashing - Laufer, William S. (Journal of business ethics, 2003)
Critics of SRI have said little about the integrity of corporate representations resulting in screening inclusion or exclusion. This is surprising given social and environmental accounting research that finds corporate posturing and deception in the absence of external verification, and a parallel body of literature describing corporate "greenwashing" and other forms of corporate disinformation. In this paper I argue that the problems and challenges of ensuring fair and accurate corporate social reporting mirror those accompanying corporate compliance with law. Similarities and points of convergence between social reporting and corporate compliance are discussed, along with proposals for reform.